A review of the literature on extracranial carotid artery aneurysms - Roos A.M. van Heeswijk, MD; Edwin Stephen, MD; Palma M. Shaw, MD; Wei Zhou, MD; Satyendra G. Ramnadh, MD; Prem C. Gupta, MD; Gert J. de Borst, MD, PhD (JVS-Vascular Insights)
Extracranial carotid artery aneurysm (ECAA) is a rare vascular pathology affecting the carotid artery; it is often discovered incidentally. Diverse etiologies of ECAAs have been reported, resulting in a wide range of symptoms that vary in onset, severity, and presentation. Asymptomatic patients can often be managed conservatively, whereas invasive treatment is indicated for symptomatic patients or those with signs of aneurysm enlargement. Invasive treatment options for ECAAs include surgical, endovascular, and hybrid approaches, depending on patient and disease characteristics. Future evidence from large case series is needed to obtain information regarding the natural course of ECAAs and to define a standardized treatment approach.